Hepatitis A Vaccine Effectiveness and Seropositivity Among 1- to 18-Year-Old Children: 10-Year Results - Samanci, Serhat; Akdeniz, Osman (Aves, 2022)
Objective: The aim of the study was to examine and compare hepatitis A seropositivity in children. Materials and Methods: The study included patients aged 0-18 years who presented to our hospital and were examined for hepatitis A virus serology between 2009 and 2018. Patients were separated into 2 groups: those who presented before (group I) or after (group II) September 2012, when the mandatory hepatitis A vaccination program came into effect in Turkey. Results: In total, 34 809 patients were evaluated: 20 111 (57.8%) males and 14 698 (42.2%) females, with a mean age of 8.2 +/- 5.3 years. Anti-hepatitis A virus immunoglobulin M positivity was observed in 3.3% of patients, most often in January and from January to April when the region experiences more rainfall. Anti-hepatitis A virus immunoglobulin M positivity decreased dramatically in group II compared to group I (0.26% vs. 7.42%, P < .001). Anti-hepatitis A virus immunoglobulin G positivity was observed in 53.8% of all patients. A statistically significant increase was determined in anti-hepatitis A virus immunoglobulin G seropositivity in group II compared to group I (81.9% vs. 42.1%, P < .001). Conclusion: Hepatitis A virus infection in Turkey decreased dramatically following improvements to infrastructure and sanitation and implementation of the vaccination program. This study is the most comprehensive report of hepatitis A seropositivity in Turkey to date.
Keywords: Children; HAV seropositivity; vaccination